2004
DOI: 10.1002/pros.20071
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mouse with human mutant p53 expression in the prostate epithelium

Abstract: Background Apoptosis is disrupted in prostate tumor cells, conferring a survival advantage. p53 is a nuclear protein believed to regulate cancer progression, in part by inducing apoptosis. To test this possibility in future studies, the objective of the present study was to generate a transgenic mouse model expressing mutant p53 in the prostate (PR). Methods Transgene incorporation was tested using Southern analysis. Expression of mutant p53 protein was examined using immunofluorescence microscopy. Apoptosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…According to earlier studies with mouse models, conditional inactivation of Rb or transgenic expression of mutant p53 results in development of prostatic hyperplasia and intraepithelial neoplasia (9,10), which is consistent with our data. However, contrary to our work, prostate epithelium-specific conditional knockout of p53 using PB-Cre4 mice did not result in any obvious phenotype by 18 months of age in one study (8).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to earlier studies with mouse models, conditional inactivation of Rb or transgenic expression of mutant p53 results in development of prostatic hyperplasia and intraepithelial neoplasia (9,10), which is consistent with our data. However, contrary to our work, prostate epithelium-specific conditional knockout of p53 using PB-Cre4 mice did not result in any obvious phenotype by 18 months of age in one study (8).…”
Section: Discussionsupporting
confidence: 93%
“…Conditional inactivation of p53 does not lead to any neoplastic phenotype (8) whereas expression of the human mutant p53 results in prostatic intraepithelial neoplasia (PIN; ref. 9). Rb loss of function results in hyperplasia after Rb inactivation in situ (10) or carcinoma after transplantation of Rb-deficient cells as a prostatic graft (11).…”
Section: Introductionmentioning
confidence: 99%
“…Elgavish et al used a gene encoding a mutant p53, placed under the control of the rat probasin promoter to study the role of p53 mutations in PCa. The resulting transgenic mice exhibited HGPIN lesions (grade III-IV) by 52 weeks of age together with reduced apoptotic potential (Elgavish, et al 2004). …”
Section: Genetically Engineered Mouse Modelsmentioning
confidence: 99%
“…Numerous transgenic models have been generated with tumor suppressor genes, p53 and retinoblastoma (Rb), as the primary candidates. A gene encoding a mutant p53 was placed under the control of the rat probasin promoter, and the resulting transgenic mice exhibited HGPIN lesions (grade III-IV) by 52 weeks of age together with reduced apoptotic potential [97]. Targeted deletion of Rb showed that the conditional loss of even a single allele of this gene in the prostate epithelial cells causes focal hyperplasia, providing a model for studies of early stage PC [98].…”
Section: Modulation Of Cell Cycle and Apoptosis Gene Expressionmentioning
confidence: 99%